1996
DOI: 10.2466/pr0.1996.79.1.127
|View full text |Cite
|
Sign up to set email alerts
|

Association of Depressive Symptoms and School Adolescents' Smoking: A Cross-Lagged Analysis

Abstract: This study examined the association of depressive symptoms of adolescents and their smoking behavior. A national cohort sample of school adolescents (N = 5,855) who participated in the 1989 and 1993 Teenage Attitudes and Practices Survey was obtained. The information from this survey included measures of smoking behavior and a series of factors related to depressive symptoms during a 3-yr. span. A cross-lagged analysis with Kendall tau b correlations was used. Judging from the magnitude of the cross-lagged cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 5 publications
4
24
0
5
Order By: Relevance
“…Five of eight longitudinal studies found the statistically significant relationships between smoking and depression: Three studies found depression as an antecedent to smoking, and two studies found the bidirectional relationship between smoking and depression (Dierker et al, 2004;Fleming et al, 2002;Gilpin et al, 2004;Goodman & Captman, 2000;Wang et al, 1996). Despite the fact that the majority of the 18 studies found a statistically significant relationship between smoking and a putative measure of depression, these significant relationships may not reflect the same processes that are assessed with more valid measures of depression.…”
Section: Measurement Of Depressionmentioning
confidence: 79%
See 1 more Smart Citation
“…Five of eight longitudinal studies found the statistically significant relationships between smoking and depression: Three studies found depression as an antecedent to smoking, and two studies found the bidirectional relationship between smoking and depression (Dierker et al, 2004;Fleming et al, 2002;Gilpin et al, 2004;Goodman & Captman, 2000;Wang et al, 1996). Despite the fact that the majority of the 18 studies found a statistically significant relationship between smoking and a putative measure of depression, these significant relationships may not reflect the same processes that are assessed with more valid measures of depression.…”
Section: Measurement Of Depressionmentioning
confidence: 79%
“…Six longitudinal studies investigating a bidirectional relationship between smoking and depression reached inconsistent results. Some studies found a bidirectional relationship (Brown, Lewinsohn, Seeley, & Wagner, 1996;Wang, Fitzhugh, Turner, Fu, & Westerfield, 1996;Windle & Windle, 2001), but the others found unidirectional relationships, either depression as a predictor of smoking or smoking as a predictor of depression (Goodman & Captman, 2000;Patton, Carlin, Coffey, & Wolfe, 1998;Wu & Anthony, 1999). Brown et al (1996) investigated the effects of smoking at Time 1 (i.e., those who smoked three or more times per week vs. those who smoked two or less times per week) on the incidence of depression between Time 1 and Time 2 among those who did not experience depression at Time 1.…”
Section: Directions Of Associations Between Smoking and Depressionmentioning
confidence: 99%
“…Imidlertid foreligger det nå flere longitudinelle studier blant ungdom der det er vist at depresjoner eller høy skåre på skalaer som måler depressivitet predikerer røyking på senere tidspunkt (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34).…”
Section: Innledningunclassified
“…Wang et al (33) ser på tidsforskjøvne assosiasjoner (cross lagged associations) mellom røyking og depressivitet på ett tidspunkt og de samme variablene 4 år se-nere. De finner at de to tidsforskjøvne sammenhengene målt med Kendalls tau begge var statistisk signifikante og omtrent like store.…”
Section: Innledningunclassified
See 1 more Smart Citation